Strength model for end cover separation failure in RC beams strengthened with near-surface mounted (NSM) FRP strips. (1st March 2016) - Teng, J.G.; Zhang, S.S.; Chen, J.F.
Highlights: End cover separation in RC beams strengthened with NSM FRP strips is studied. An efficient FE model based on the concrete tooth concept was used in the study. A strength model is proposed on the basis of results form an FE parametric study. The proposed model agrees closely with available test results. The proposed model is far more accurate than existing models. Abstract: As an alternative to externally bonded FRP reinforcement, near-surface mounted (NSM) FRP reinforcement can be used to effectively improve the flexural performance of RC beams. In such FRP-strengthened RC beams, end cover separation failure is one of the common failure modes. This failure mode involves the detachment of the NSM FRP reinforcement together with the concrete cover along the level of the tension steel reinforcement. This paper presents a new strength model for end cover separation failure in RC beams strengthened in flexure with NSM FRP strips (i.e. rectangular FRP bars with a sectional height-to-thickness ratio not less than 5), which was formulated on the basis of extensive numerical results from a parametric study undertaken using an efficient finite element approach. The proposed strength model consists of an approximate equation for the debonding strain of the FRP reinforcement at the critical cracked section and a conventional section analysis to relate this debonding strain to the moment acting on the same section (i.e. the debonding strain). Once the debonding strain is known, the load level at end cover separation of an FRP-strengthened RC beam can be easily determined for a given load distribution. Predictions from the proposed strength model are compared with those of two existing strength models of the same type and available test results, which shows that the proposed strength model is in close agreement with test results and is far more accurate than the existing strength models.